2011
DOI: 10.5152/akd.2011.162
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological conversion of recent atrial fibrillation: a randomized, placebo-controlled study of three antiarrhythmic drugs

Abstract: ÖZETAmaç: Atriyal fibrilasyonun (AF) sinüs ritmine döndürülmesi çoğu kez emboli riskini ve hemodinamik bozulmanın azaltılması için yapılır. Bu çalışmada, son 48 saat içinde AF geçirmiş hastalar üzerinde tek oral doz flekainid, amiyodaron ve propafenon ile atriyal fibrilasyonun sinüs ritmine dönüşümü üzerindeki etkileri plasebo ile randomize olarak karşılaştırılmıştır. Yöntemler: Bu çalışma 160 hasta üzerinde yapılmış, hastalara rastgele olmak üzere flekainid (3 mg/kg, n=40), amiyodaron (30 mg/kg, n=40), propaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…However, it is important to note that especially in studies comparing amiodarone against faster acting AADs the window of observation has an impact on the outcome. Some studies stopped after 90 min whereas the effect of amiodarone takes a longer time, resulting in low cardioversion rates of amiodarone compared to studies with a longer observation period (Martínez-Marcos et al, 2000;Balla et al, 2011;Camm et al, 2011). Amiodarone is a multi-channel blocker, inhibiting inward sodium (I Na ) and calcium channel currents (I Ca ) as well as voltage-and ligand-gated potassium channel currents (I K , I KNa , I KACh ) (Kodama et al, 1999) and the two-pore domain potassium channel TASK-1 (I TASK-1 ) (Gierten et al, 2010).…”
Section: Class III Aadsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that especially in studies comparing amiodarone against faster acting AADs the window of observation has an impact on the outcome. Some studies stopped after 90 min whereas the effect of amiodarone takes a longer time, resulting in low cardioversion rates of amiodarone compared to studies with a longer observation period (Martínez-Marcos et al, 2000;Balla et al, 2011;Camm et al, 2011). Amiodarone is a multi-channel blocker, inhibiting inward sodium (I Na ) and calcium channel currents (I Ca ) as well as voltage-and ligand-gated potassium channel currents (I K , I KNa , I KACh ) (Kodama et al, 1999) and the two-pore domain potassium channel TASK-1 (I TASK-1 ) (Gierten et al, 2010).…”
Section: Class III Aadsmentioning
confidence: 99%
“…The mean time to cardioversion ranged from 110 to 190 min after oral administration and 25–52 min after intravenous infusion ( Madrid et al, 1993 ; Reisinger et al, 1998 ; Alp et al, 2000 ; Martínez-Marcos et al, 2000 ; Khan, 2003 ; Reisinger et al, 2004 ; Balla et al, 2011 ; Bash et al, 2012 ). Flecainide has been shown to be superior to propafenone and amiodarone in both time and rate of cardioversion ( Martínez-Marcos et al, 2000 ; Balla et al, 2011 ), similar to ibutilide ( Reisinger et al, 2004 ), and inferior to vernakalant ( Pohjantähti-Maaroos et al, 2019 ). The most common adverse events during a therapy with flecainide are dizziness (30%), visual disturbance (28%), headache (9%), and nausea (9%).…”
Section: Rhythm Control Therapymentioning
confidence: 99%
“…Compared to placebo and other AADs (e.g. : amiodarone, propafenone, quinidine, sotalol) flecainide, have been found safe and effective in restoring SR in recent-onset AF [51,[68][69][70][71].…”
Section: Flecainide and Propafenone Intravenous Regimen And Pill-in Tmentioning
confidence: 98%
“…Despite the not favorable pharmacokinetic profile, amiodarone has also been tested for CV with acute oral loading [84]. Balla et al [69] analyzed 160 patients and found a conversion rate at 24 h of 85% with amiodarone, 87.5% with flecainide, 85% with propafenone and 17.5% with placebo. Similar results were reported by Peuhkurinen et al [85], in 62 patients with 87% conversion rate at 24 h with amiodarone (35% with placebo).…”
Section: Intravenous and Oral Amiodaronementioning
confidence: 99%
“…13,14 In addition, recent studies have reported an association between EFT and AF recurrence and success of electrical cardioversion. 15,16 Because the conversion time with amiodarone is longer than with other antiarrhythmic drugs, 7,9,17 the determination of early conversion predictors is crucial in terms of length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%